EDUKASI PENGEMBANGAN UMKM GUNA MENINGKATKAN PROFITABILITAS MASYARAKAT DESA MARGALUYU - Putri, Sri Novianti Putri; Dede Rizal Munir; Ade Irvi Nurul Husna (Jurnal Pendekar Nusantara, 2024)
The development of Micro, Small and Medium Enterprises (MSMEs) has been recognized as one of the main motors of local economic growth in many countries, including at the village level. In a village context, MSMEs are often the backbone of the economy, creating jobs, increasing income, and strengthening social and cultural networks. However, to maximize the potential of MSMEs in increasing village profitability, real efforts are needed in education and skills development for business owners at the local level. The growth of Micro, Small and Medium Enterprises (MSMEs) has an important role in developing the local economy, especially in rural areas. Villages are often places where a variety of local economic potential resides which can be utilized to improve community welfare. However, MSMEs at the village level often face various challenges, such as limited access to capital, limited managerial skills, and lack of knowledge about markets and technology. Education and skills development are the keys to overcoming these challenges and increasing the profitability of MSMEs in villages. By increasing the capacity of business owners and local economic actors, it is hoped that MSMEs can be more competitive, competitive and able to make a greater contribution to village economic growth.